The Correlation Between Frequency of Protein Consuption and Incidence of Intradialysis Hypertension in Hemodialysis Unit of Ade M Jhon Hospital Sintang - Suwito, Kafi Pangki; Yati, Asri Fitri (Journal of World Future Medicine, Health and Nursing, 2023)
Kidney disease is one of the primary causes of mortality and disability in many countries throughout the world. Protein consumption may worsen kidney damage because the most dangerous metabolism is the concentration of blood urea nitrogen. Currently, hemodialysis is one of the renal replacement therapies, but the most frequent complication in dialysis is hypertension, which may increase morbidity and mortality. Objective: To identify the correlation between frequency of protein consumption and incidence of intradialytic hypertension in the hemodialysis unit of Ade M Jhon Hospital Sintang. Methods: This research is quantitative with a cross-sectional design. The population in this research was 177 respondents based on medical records, while sampling employed purposive sampling which was taken in 66 respondents with chronic renal failure in the Hemodialysis Unit of Ade M Jhon Hospital Sintang. The statistical test in this study employed chi-square, with an error rate of ? of 5% (0.05). Results: Most frequency of protein consumption with intradialytic hypertension categorized as rare was 12 respondents (18.18%) who did not suffer from hypertension and 3 respondents (4.55%) who suffered from hypertension, while categorized as frequent was 49 respondents (74.24%) who suffered from hypertension and 2 respondents (3.03%) who did not suffer from hypertension. The significant value of the variable of protein consumption frequency with intradialytic hypertension was P value of 0.000 <0.05 (?).